1997
DOI: 10.1117/12.298148
|View full text |Cite
|
Sign up to set email alerts
|

<title>Analysis of hydrological changes in lakes of Asian arid zone by satellite data</title>

Abstract: This paper cscribes a method and results for the investigation of the recent hydrological changes in Aral Sea and Lake Balkhash of Central Asia using multi-temporal satellite data. Landcover change of the lakes and their vicinity from 1960's to 1990's were analyzed by comparing the lan&over classification images. Using the analyzed satellite images, a bathymetric map and the meteorological observations, change estimation of water volume and levels, and analysis of water balance in lakes were carried out.It is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Harris (1994) correlated the variation of water levels in a lake with precipitation and evaporation as an aid in his climate research. The interaction between hydrological changes observed in Lake Aral and certain regional environmental parameters has been studied by Nakayama et al (1997). Vázquez et al (2003) have studied the pattern of observed water surface area in relation with antecedent precipitation as a means for drawing zone maps that indicate flood frequencies.…”
Section: Introductionmentioning
confidence: 99%
“…Harris (1994) correlated the variation of water levels in a lake with precipitation and evaporation as an aid in his climate research. The interaction between hydrological changes observed in Lake Aral and certain regional environmental parameters has been studied by Nakayama et al (1997). Vázquez et al (2003) have studied the pattern of observed water surface area in relation with antecedent precipitation as a means for drawing zone maps that indicate flood frequencies.…”
Section: Introductionmentioning
confidence: 99%
“…Changes in the water extent of playas and closed salt lakes have been estimated by remote sensing to asses changes in regional climate (Schneider et al 1985;Harris, 1994;Bryant, 1999;Birkett, 2000). Nakayama et al (1997) detected changes in the water area and volume of Central Asian lakes and related them to environmental parameters. Remote sensing provides a temporal perspective of the playa-lakes hydrology in the lack of historical data such as water levels (Al-Khudhairy et al, 2002).…”
Section: Introductionmentioning
confidence: 99%